Enzymatic production of 4-hydroxyphenylacetaldehyde by oxidation of the amino group of tyramine with a recombinant primary amine oxidase. (May 2020) - Yu, Tianqi; Yin, Yifan; Ge, Yihe; Cheng, Shiwei; Zhang, Xingxiao; Feng, Zhibin; Zhang, Juan
Graphical abstract: Highlights: A biphasic system was developed to relieve product inhibition. An obviously higher concentration of tyramine (120 mM) was used in the biphasic system than in the aqueous system. 4-Hydroxyphenylacetaldehyde was obtained in 76.5 % yield (91.8 mM) in the biphasic system. Abstract: In this study, an efficient enzymatic process for the synthesis of 4-hydroxyphenylacetaldehyde (4-HPAA) from tyramine was developed using whole cells of recombinant Escherichia coli co-expressing primary amine oxidase (PrAO) from E. coli and catalase (CAT) from Bacillus pumilus . The reaction conditions for the synthesis of 4-HPAA were systematically optimized starting from a monophasic aqueous buffer. The optimum reaction temperature, pH, and biocatalyst loading were 33 °C, 7.5, and 20 g/L wet cells, respectively. Substrate feeding strategies were employed to alleviate substrate inhibition, providing a 14.8 % increase in yield. A biphasic catalytic system was explored to avoid product inhibition and thus further improve the 4-HPAA yield. Ethyl acetate was found to be the best organic solvent, and the optimum volume ratio of the organic phase to the aqueous phase was 40 % (v/v). Under the optimized conditions on a 1 L scale, a yield of 76.5 % was obtained with a substrate concentration of 120 mM. Thus, the bioconversion was more efficient in the ethyl acetate/buffer biphasic system than in the monophasic aqueous system, and the yield of 4-HPAA was improved 1.89-fold.